Bio-Spectroscopic Imaging Provides Evidence of Hippocampal Zn Deficiency and Decreased Lipid Unsaturation in an Accelerated Ageing Mouse Model - Fimognari, Nicholas; Hollings, Ashley; Lam, Virginie; Tidy, Rebecca; Kewish, C.; Albrecht, Matthew; Takechi, Ryu; Mamo, John; Hackett, Mark (American Chemical Society, 2018)
© 2018 American Chemical Society. Western society is facing a health epidemic due to the increasing incidence of dementia in ageing populations, and there are still few effective diagnostic methods, minimal treatment options, and no cure. Ageing is the greatest risk factor for memory loss that occurs during the natural ageing process, as well as being the greatest risk factor for neurodegenerative disease such as Alzheimer's disease. Therefore, greater understanding of the biochemical pathways that drive a healthy ageing brain towards dementia (pathological ageing or Alzheimer's disease), is required to accelerate the development of improved diagnostics and therapies. Unfortunately, many animal models of dementia model chronic amyloid precursor protein over-expression, which although highly relevant to mechanisms of amyloidosis and familial Alzheimer's disease, does not model well dementia during the natural ageing process. A promising animal model reported to model mechanisms of accelerated natural ageing and memory impairments, is the senescence accelerated murine prone strain 8 (SAMP8), which has been adopted by many research group to study the biochemical transitions that occur during brain ageing. A limitation to traditional methods of biochemical characterisation is that many important biochemical and elemental markers (lipid saturation, lactate, transition metals) cannot be imaged at meso- or micro-spatial resolution. Therefore, in this investigation we report the first multi-modal biospectroscopic characterisation of the SAMP8 model, and have identified important biochemical and elemental alterations, and co-localisations, between 4 month old SAMP8 mice and the relevant control (SAMR1) mice. Specifically, we demonstrate direct evidence of altered metabolism and disturbed lipid homeostasis within corpus callosum white matter, in addition to localised hippocampal metal deficiencies, in the accelerated ageing phenotype. Such findings have important implication for future research aimed at elucidating specific biochemical pathways for therapeutic intervention.